CORRELATIONS OF VOLITIONAL SELF-CONTROL WITH CERTAIN DIMENSIONS OF PUPIL’S PERSONALITY - Paladi Oxana; Lungu Tatiana (International Journal of Innovative Technologies in Social Science, 2024)
In this article, the correlations of volitional self-control with certain dimensions of pupil’s personality are presented. The basic concept, volitional self-control, outlines several component scales, namely the general self-control index, self-mastery, and perseverance. Moreover, this paper highlights the premise that authors state self-control as one of the key elements that define a person's willpower. In the specialty literature, we encounter a series of references to similar concepts, such as willpower, self-control, self-regulation, but these are not sufficiently integrated to generate a comprehensive picture of willpower that addresses details regarding relationships with other processes. Thus, we considered this research appropriate to identify the relationship of volitional self-control with other dimensions of personality (anxiety, depression, loneliness, somatic complaints, self-confidence, social courage, initiation of social contacts, etc.) from the perspective of contemporary societal approaches. We mention that the present study is conducted on a sample of 304 pupils from general education institutions in the Republic of Moldova.